Caso Clínico ARP nº 26: Qual o seu diagnóstico? - Silva, João Santos (2022)
A 68-year-old woman with a history of arterial hypertension and Gilbert´s syndrome was referred to a Gastroenterology consultation due to adenomyomatosis of the gallbladder. Additionally, laboratory results reveal changes on liver tests and an abdominal computed tomography (CT) was initially performed. An incidentaloma on the second part of the duodenum was described (arrow). Then, the upper digestive endoscopy did not reveal any significant alteration and an abdominal magnetic resonance imaging (MRI) was performed for further investigation of this lesion. What is your diagnosis?